Solitary juvenile xanthogranuloma of the cervical spine in a child: A case report and review of literature - Bhaisora, Kamlesh; Jaiswal, Awadhesh; Mehrotra, Anant; Sahu, Rabi; Srivastava, Arun; Jaiswal, Sushila; Behari, Sanjay (Asian Journal of Neurosurgery, 2015)
The authors present a case of 15 years male child who presented with neck pain and progressive ascending quadriparesis. Magnetic resonance imaging showed lytic mass involving C5 and C6 vertebra with soft tissue extension. Surgical excision of mass done using anterior cervical approach. Postoperatively, patient showed improvement in spasticity and power. Histopathological examination of mass was suggestive of juvenile xanthogranuloma (JXG). At 6 months follow-up, patient was improving without any evidence of recurrence. Only 12 cases of JXG of spine have been reported till date including only four cases involving the cervical spine and among these four cases only two were of pediatric age group.
Keywords: Cervical vertebra; histology; myelopathy; surgery; xanthogranuloma